KAJIAN KONSENTRASI DAN LAMA PERENDAMAN COLCHICINE TERHADAPJANAMAN TOMAT (Solanum Iycopersicum. L) - Dewanti, F. Deru; Koentjoro, Yonny; -, Moegijanto (MAPETA, 2000)
The using of chemical materials on plant could be increasing or decreasing on production of plant, studies of it is often written on many scientific magazines with variation results. Colchicine as mutagent could Influence on several growth processes of plant e.g. : elongation cell and duplication cromosome of cell processing. This research is arranged in Completely Randomized Design with two factors and three times replcation, LSD test 5 % is used to compare the difference of every treatments. As the first factor is Concentration of Colchicine With four levels are: KO(0.00 % Colchicine), K1 (0.1 % Colchicine), K2 (02 % Colchicine) and K3 (0.3 % Colchicine), as the second factor is period of soaking of tomato seed with four levels are L1 (24 hours), L2 (48 hours), L3 (72 hours) and L4 (96 hours). Results of this research shown that there were significant Interaction between Concentration Colchicine an period of soaking on normal seedling percentage, time of seedling, height of plant on 30 days after planting, number of leafes on 58 days after planting, flowering age. Keywords :Tomato, concentration, colchicine